(untitled) (Modern education and development, 2025)
Abdulla Oripovning “Onajon” she’ri insoniy tuyg‘ularning eng beg‘ubor shakllaridan biri bo‘lmish ona mehri, uning yo‘qligidan kelib chiqadigan chuqur iztirob va farzandlik mehri bilan yo‘g‘rilgan. Ushbu asar shoir ijodining eng ezgu va yurakka yaqin namunalardan biri bo‘lib, unda inson hayotining eng yuksak qadriyatlari haqida mulohaza yuritiladi. Abdulla Oripov’s poem "Mother" is composed of one of the most innocent forms of human feelings, mother’s love, deep suffering and filial love caused by her absence. This work is one of the most beautiful and close to the heart examples of the poet’s work, which reflects on the highest values ​​of human life.